Phytochemical and Antioxidant Activity of Lemongrass Stem Extract and Cream Analysis by Fourier Transform Infrared - Suaniti*, Ni Made; Riasa, I Nyoman Putu; Puspawati, Ni Made; Samirana, Oka; Wahab, Roswanira Abdul; Valineli, Samanthi Elani; Aryasuadnyana, I Nyoman Krisnanda (Universitas Syiah Kuala, 2025)
Lemongrass is one of the plants that grows in Indonesia, is easy to find, and contains active compounds with potential antioxidant properties. The aim of this study was to analyze phytochemical and antioxidant activity of lemongrass stem extract and functional groups in its cream formulation. The lemongrass stems were extracted using the maceration method with 96% ethanol as the solvent, and the resulting extract was evaporated to obtain a thick lemongrass stem extract. The method of analyze the lemongrass stem extract and the cream formulation was carried out using phytochemical screening and antioxidant activity tests were performed on the lemongrass stem extract against 2,2-diphenyl-1-picrylhydrazyl as a free radical and measured at a wavelength of 517 nm using a UV-Vis spectrophotometer. The cream base, and the cream containing the lemongrass stem extract ware tested by fourier transform infrared spectrophotometer to identify functional groups in the extract and cream was conducted using the KBr pellet method. The results showed that the cream with 10% lemongrass stem extract had the strongest antioxidant activity compared to the 7.5 and 5% concentrations, with an IC50 value of 722.12 ppm, which is categorized as weak antioxidant activity. Functional group analysis showed that the cream without the addition of lemongrass stem extract had no absorption or detectable functional groups, whereas the three creams with lemongrass stem extract showed increased transmittance, with the presumed functional groups being hydroxyl (OH), methyl (CH3), and carbonyl (C=O)